2016
DOI: 10.14689/ejer.2016.66.2
|View full text |Cite
|
Sign up to set email alerts
|

The Communication Barriers between Teachers and Parents in Primary Schools

Abstract: Problem Statement: In educational institutions, the effectiveness of communication between teachers and parents, in terms of student achievement and attendance, has a great importance. Parent-teacher communication provides multi-faceted benefits to teachers, the school, and parents as well. However, various obstacles hinder the realization of effective parent-teacher communication in school settings. Purpose of Study:The main purpose of this study is to determine the communication barriers between parents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 7 publications
2
32
0
8
Order By: Relevance
“…This finding is in contrast to the study of Lipsky, Friedman and Harkema (2017) who mentioned that teachers believe parental involvement is the key for cooperative partnerships as long as that parental involvement does not threaten a teacher's professional authority. In the same way, the study of Ozmen, Akuzum, Zincirli, et. al (2016) stated that the school and teachers adopt an open-door policy for parents; and the schools collaborate with the parents, staff and other stakeholders.…”
mentioning
confidence: 78%
“…This finding is in contrast to the study of Lipsky, Friedman and Harkema (2017) who mentioned that teachers believe parental involvement is the key for cooperative partnerships as long as that parental involvement does not threaten a teacher's professional authority. In the same way, the study of Ozmen, Akuzum, Zincirli, et. al (2016) stated that the school and teachers adopt an open-door policy for parents; and the schools collaborate with the parents, staff and other stakeholders.…”
mentioning
confidence: 78%
“…When working with children, professionals encounter a variety of family dynamics and cultures to which they need to adapt. There are existing barriers that can negatively affect the communication process (Ozmen et al, 2016). Participants stated the need for additional experiences that allow them to interact with parents in order to learn how to address complicated situations and improve their sensitivity to delicate topics.…”
Section: Discussionmentioning
confidence: 99%
“…Effective partnerships result in positive outcomes in the socioemotional and academic development of children (Berger, 2008;Evans, 2013;Shannon, Bishop, Snyder, & Jaramillo, 2019). However, existing barriers make this task complex (Ozmen, Akuzum, Zincirli, & Selcuk, 2016). Families come from more diversified sociocultural contexts than professionals have experienced (Dotger, 2010).…”
mentioning
confidence: 99%
“…Findings from other studies have also shown that communication, whether written or oral, gives parents a better understanding of policies, procedures and programs within the school, which allows for additional support of the school. Effective dialogue "develops out of a growing trust, a mutuality of concern, and an appreciation of contrasting perspectives" (Ozmen, Akuzum, Zincirli, and Selcuk, 2016). As parents communicate with the school they typically become more comfortable and satisfied with the school and the teachers (Epstein et al, 2009).…”
Section: Parents' Communication With Schoolmentioning
confidence: 99%